Immigrant influx and social cohesion erosion - Florence Neymotin (IZA Journal of Migration, 2014)
If immigration causes a decrease in social cohesion, then it may also be an important contributing factor in the recent failure of financial institutions. The present analysis finds some evidence for a negative relationship between immigration and volunteering from the Current Population Survey 2004 - 2008 September Supplements. Various specifications confirm the tendency of immigrant inflows to decrease social cohesion, as measured by the tendency of native US citizens to volunteer. Differences in effect by type of volunteering organization, country of origin of immigrants, functional form, and voting as the relevant measure of social cohesion are explored with similar patterns of results. Differences in effect by city size provide a counterpoint, lending support to the alternative idea that immigration does not in fact decrease social cohesion.
Keywords: H8; Z13; J61; 330; Social cohesion; Volunteering; Immigration